Crystal Structure of the Extracellular Domains of GPR110. Issue 6 (15th March 2023) - Wang, Fangfang; Wang, Yang; Qiu, Weicheng; Zhang, Qiansen; Yang, Huaiyu; Song, Gaojie
Graphical abstract: Highlights: The extracellular domains of GPR110 was solved at 2.9 Å resolution. Crystal structure reveals atomic details for the domain connections between SEA, HormR, and GAIN domains. A N-linked glycosylation on N389 is critical for the folding and secretion of GPR110. Docking of ligand synaptamide on GPR110 shed light on potential activation mechanism. Abstract: Adhesion G protein-coupled receptors (aGPCRs) play a pivotal role in human immune responses, cellular communication, organ development, and other processes. GPR110 belongs to the aGPCR subfamily VI and was initially identified as an oncogene involved in lung and prostate cancers. GPR110 contains tandem adhesion domains at the extracellular region that mediate inter-cellular signaling. However, the structural organization and signaling mechanism for these tandem domains remain unclear. Here, we report the crystal structure of a GPR110 fragment composing the SEA, HormR, and GAIN domains at 2.9 Å resolution. The structure together with MD simulations reveal rigid connections between these domains that are stabilized by complementary interfaces. Strikingly, we found N-linked carbohydrates attached to N389 of the GAIN domain form extensive contacts with the preceding HormR domain. These interactions appear to be critical for folding, as removal of the glycosylation site greatly decreases expression of the GPR110 extracellular fragment. We further demonstrate that the ligand synaptamide fits well within the hydrophobic pocket occupied by the Stachel peptide in the rest state. This suggests that the agonist may function by removing the Stachel peptide which in turn redocks to the orthosteric pocket for receptor activation. Taken together, our structural findings and analyses provide novel insights into the activation mechanism for aGPCRs.